2023
DOI: 10.3390/ijms241813948
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Progress, and Treatment Update of Kawasaki Disease

Ho-Chang Kuo

Abstract: Kawasaki disease (KD) is an acute inflammatory disorder that primarily affects children and can lead to coronary artery lesions (CAL) if not diagnosed and treated promptly. The original clinical criteria for diagnosing KD were reported by Dr. Tomisaku Kawasaki in 1967 and have been used for decades. However, research since then has highlighted the limitations of relying solely on these criteria, as they might lead to underdiagnosis or delayed diagnosis, potentially increasing the risk of coronary artery compli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Numerous studies examining eosinophils' role in KD suggest that elevated eosinophil counts may induce allergic diseases, thus contributing to CAD. Kuo et al reported in their study that the eosinophil count is an important factor in distinguishing KD from other febrile diseases [41]. In a study reported in 2023, eosinophils have been found to possess a relative predictive value for coronary artery dilation.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies examining eosinophils' role in KD suggest that elevated eosinophil counts may induce allergic diseases, thus contributing to CAD. Kuo et al reported in their study that the eosinophil count is an important factor in distinguishing KD from other febrile diseases [41]. In a study reported in 2023, eosinophils have been found to possess a relative predictive value for coronary artery dilation.…”
Section: Discussionmentioning
confidence: 97%
“…The most serious complication of KD is coronary artery damage, which is also an important risk factor for ischemic heart attack in adulthood ( 28 ). The coronary artery is a common invasive site of KD, that can cause destruction, dilatation, rupture, stenosis, and even embolism of the vascular wall ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latest national survey conducted by the Japan Circulation Society (JCS) shows that 7% of children with KS present vascular complications in the acute phase, and 2.3% develop cardiovascular sequelae after discharge [ 7 ]. About 20-25% of untreated cases will develop into severe CAL, which makes KS the most common cause of pediatric acquired heart disease in developed countries [ 8 ]. Therefore, it is necessary to carry out CAL risk prediction stratification for early diagnosis and intensive care.…”
Section: Introductionmentioning
confidence: 99%